2013
DOI: 10.1097/jto.0b013e3182781e35
|View full text |Cite
|
Sign up to set email alerts
|

Compound EGFR Mutations and Response to EGFR Tyrosine Kinase Inhibitors

Abstract: INTRODUCTION Non-small-cell lung cancers (NSCLCs) containing epidermal growth factor receptor (EGFR) mutations are exquisitely sensitive to EGFR tyrosine kinase inhibitors (TKIs). This is the case of the most common EGFR mutations affecting exon 18 (G719X), 19 (inframe deletions) and 21 (L858R and L861Q). However, the frequency of compound (i.e., double or complex) EGFR mutations - where an EGFR TKI sensitizing or other mutation is identified together with a mutation of unknown clinical significance – and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
142
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 19 publications
9
142
3
2
Order By: Relevance
“…By contrast, a positive clinical response to gefitinib in an NSCLC patient harboring the rare mutation p.S768I was observed by Masago et al (25). Additional previous studies have also reported partial responses to EGFR-TKIs in patients exhibiting p.S768I and other mutations (8,20,23,29,30). In addition, a number of retrospective analyses of EGFR mutations (Table I) have investigated the p.S768I mutation; however, the clinical responsiveness to EGFR-TKIs has not been reported (7,12,13,26,31).…”
mentioning
confidence: 62%
“…By contrast, a positive clinical response to gefitinib in an NSCLC patient harboring the rare mutation p.S768I was observed by Masago et al (25). Additional previous studies have also reported partial responses to EGFR-TKIs in patients exhibiting p.S768I and other mutations (8,20,23,29,30). In addition, a number of retrospective analyses of EGFR mutations (Table I) have investigated the p.S768I mutation; however, the clinical responsiveness to EGFR-TKIs has not been reported (7,12,13,26,31).…”
mentioning
confidence: 62%
“…These mutations encompass EGFR-exon 18 indels/E709X (<0.5% of EGFR mutations), exon 18 G719X (~3% of EGFR mutations), exon 19 insertions (<0.5% of EGFR mutations), exon 20 A763_ Y764insFQEA (<0.5% of EGFR mutations), exon 20 S768I (<1.5% of EGFR mutations) and the exon 21 L861Q (~3% of EGFR mutations); either alone or compound with other EGFR mutations (19). It is interesting to note that in preclinical models, the inhibitory concentrations of 1 (23) when compared to EGFR-exon 19 deletion mutants.…”
mentioning
confidence: 99%
“…This E709A mutation, undetected in the first molecular diagnosis made by pyrosequencing procedure in another Italian Hospital Center, was then a naïve EGFR mutation of exon 18 of EGFR gene, together with G719A. The attenuated response or less sensitivity to TKIs and downstream effector phosphorylation profiles than the EGFR mutation of codon 719 alone were demonstrated only by two studies [11,12], in tumor simple and in vitro NSCLC patients, respectively, while the more attenuated response to TKIs due to naïve co-presence of the mutations at 719 and 709 codons of the same exon was found and/or described by few reports [8,9,[13][14][15]. In particular, Tam et al (2009), found that double mutant (E709A+G719C) of EGFR, showed a response profile intermediate between those of E709A and G719C, suggesting that the presence of the uncommon E709A, in addition to the activating G719C, would confer relative resistance to gefitinib treatment [12].…”
Section: Discussionmentioning
confidence: 99%